Success of Siompu Orange Plant Shoot Cuttings With Natural Growth Regulators and Arbuscular Mycorrhzal Fungi (AMF) Application - Husna, Husna; Tuheteru, Faisal; Wiwin Rahmawati Nurdin; Asrianti Arif; Nais Mawarsyah Lauti (Journal of Tropical Mycorrhiza, 2025)
Siompu tangerine (Citrus nobilis Lour.) is an endemic plant from Siompu Island, This plant is rare and slow to bear fruit due to generally being cultivated generatively. This study aims to determine the effect of natural growth regulators combined with Arbuscular Mycorrhizal Fungi on the success of Siompu tangerine shoot cuttings. This research was conducted in the plastic house of the Indonesian Mycorrhizal Association (AMI) Southeast Sulawesi Branch Universitas Halu Oleo (UHO) and the Kendari Forestry and Environmental Sciences Laboratory Unit, which lasted for 5 months from September to February 2025. This study used a Randomized Block Design consisting of 9 treatments, namely control (a), aloe vera solution (b), shallot solution (c), AMF Inoculum of Kaimbulawa Village (d), AMF Inoculum of Lapara (e), Aloe vera solution + AMF Inoculum of Kaimbulawa Village (f), Aloe vera solution + AMF Inoculum of Lapara (g), Shallot solution + AMF Inoculum of Kaimbulawa Village (h) and Shallot solution + AMF Inoculum of Lapara ( i ) each treatment consisted of three replications and each replication consisted of five plants so that the total plants used were 135 plants. The results showed that the treatment of natural growth regulator combined with AMF had not provided significant results on the Percentage of living cuttings, the percentage of cuttings that sprouted, and the number of leaves. In the Kaimbulawa AMF treatment, it can increase the rate of rooted cuttings, and the 100% natural shallot PGR treatment combined with Lapara FMA increases root length and the percentage of AMF colonization